A1.16 Role of IL-8 and its receptor in anti-citrullinated protein antibody mediated osteoclastogenesis in ra. (24th February 2016) - Liu, Y; Krishnamurthy, A; Hensvold, AH; Joshua, V; Wähämaa, H; Sun, M; Engstrom, M; Malmström, V; Rethi, B; Jopling, LA; Catrina, AI
Abstract : Background and objectives: Circulating levels of IL-8 is related to the bone loss associated with breast cancer metastasis. Recently, we have shown that anti-citrullinated protein antibodies (ACPA) can induce osteoclastogenesis. We aimed to investigate the role of IL-8 and its receptors in mediating osteoclastogenesis in presence or absence of ACPAs Methods: IL-8 levels was measured by ELISA in serum of risk RA patients and synovial fluid samples of RA patients. CD14 positive monocytes were used to generate osteoclasts with M-CSF and RANKL. Inhibition of IL-8 and its receptor were tested with IL-8 neutralising antibody or small molecule CXCR1/2 anta-agonist (Reparixin and SCH-527123) on osteoclasts (OC) in the presence or absence of ACPA. The number of the OC's were counted in light microscope after TRAP staining. Cell counting kit 8 (CCK8) assay was performed to detect cytotoxicity. CXCR1 and CXCR2 expression was analysed using flow cytometry and immunohistochemistry during different days of osteoclasts maturation. Results: Increased IL-8 levels were observed in the serum of ACPA positive at risk RA individuals and in synovial fluid of established ACPA positive RA patients. Exogenous IL-8 dose dependently increased OC numbers in presence of RANKL. IL-8 neutralising antibody inhibited the OC numbers even in the presence of ACPA. Reparixin and SCH-527123 significantly inhibited RANKL mediated osteoclastogenesis at 100 µM concentration. No cytotoxicity of the drugs were detected with CCK8 assay. With flow cytometry, we observed CXCR1 and CXCR2 expression in the OC precursors at day 0 and in presence of RANKL the expression was completely lost at day 1 and it reappeared at day 4. Immunohistochemistry staining confirmed the CXCR1/2 expression on OC precursors. Conclusions: Our data provides insights in to the importance of IL-8 autocrine loop in RANKL and ACPA mediated OC development. IL-8 receptor blockade might be a novel way of targeting osteoclasts in RA.